2001
DOI: 10.1046/j.1460-9568.2001.01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotine on cerebellar granule neuron development

Abstract: To assess the role of nicotinic cholinergic receptors (nAChR) on neuronal maturation, nAChR expression and the direct effects of nAChR activation were examined in cerebellar external granular layer (EGL) precursors isolated in vitro. Treatment of EGL neuroblasts with nicotine elicited a concentration-dependent increase in DNA content and synthesis, implying an increase in cell numbers. Pretreatment of cultures with the nAChR antagonist dihydro-β-erythroidine (DHBE) attenuated nicotine-induced changes in DNA ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 65 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…More specifically, experimental studies have demonstrated that the dynamic sequence of morphological steps that regularly occur during CC development, mainly consisting in a progressive thinning until the disappearance of the EGL due to cell death or cell migration in the IGL, coincide with the maturation of the cholinergic system (Clos et al., 1989; Court et al., 1995). The activation of the α7-nAChR subtype appears to be particularly involved in the maturation of the granule layers (Caruncho et al., 1997; Opanashuk et al., 2001; Prestori et al., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…More specifically, experimental studies have demonstrated that the dynamic sequence of morphological steps that regularly occur during CC development, mainly consisting in a progressive thinning until the disappearance of the EGL due to cell death or cell migration in the IGL, coincide with the maturation of the cholinergic system (Clos et al., 1989; Court et al., 1995). The activation of the α7-nAChR subtype appears to be particularly involved in the maturation of the granule layers (Caruncho et al., 1997; Opanashuk et al., 2001; Prestori et al., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In mice, nicotine exposure upregulates the expression of nerve growth factor (NGF) and mRNA levels of its receptor tyrosine receptor kinase A (trkA) (Garrido et al, 2003), indicating that nicotine may enhance neuronal development. Other preclinical work suggests that neuroblasts in the cerebellum treated with nicotine increase the precursor cell's DNA synthesis significantly compared to untreated controls (Opanashuk et al, 2001), further indicating an enhancing role for nicotine in neurogenesis and myelination. Given greater rapidity of white-matter development during adolescence versus adulthood (Giedd et al, 1999), such nicotine-induced cell proliferation may differentially influence white-matter tissue structure and function across the lifespan.…”
Section: Discussionmentioning
confidence: 93%
“…A possible mechanism by which smoking could raise FA draws from the following observations: 1) white matter matures through late adolescence faster than in adulthood (Benes 1989; Bartzokis and Lu 2009;); 2) nicotine acting at nAChRs can promote glial activity or proliferation (Garrido et al 2003; Liu et al 2005; Opanashuk et al 2001); and 3) nAChRs exist in subcortical white matter (Ding et al 2004). Oligodendrocyte precursor cells but not the oligodendrocytes and astrocytes into which these precursors differentiate do express nAChRs (Rogers et al 2001; reviewed Bartzokis 2007).…”
Section: Discussionmentioning
confidence: 99%